Analisis Faktor-Faktor Terlambatnya Mahasiswa Mengikuti Perkuliahan (Studi pada mahasiswa Ilmu Al-Qur'an dan Tafsir Fakultas Ushuluddin & Studi Islam UIN Sumatera Utara Tahun 2022) - Sari, Puspita; Virly, Tri Yolanda; Alviani, Tantri Rizki; Rambe, Ade Mahri Kurniawan; Fahri, Chairul (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to analyze the factors that cause Al-Qur'an and Tafsir Science students to be late in attending lectures at the Faculty of Ushuluddin & Islamic Studies, UIN North Sumatra in 2022. The research method used is qualitative with data collection techniques through in-depth interviews and documentation study. The research results show that there are several factors that contribute to students' delays in attending lectures. These factors include internal factors such as lack of motivation, imbalance between academic demands and other activities, as well as external factors such as transportation constraints and environmental conditions. This research also identified that social support and motivation from lecturers, family and the environment can play an important role in helping students overcome delays in attending lectures. The implication of these findings is the need for greater efforts from various parties, both universities and other related parties, in providing support and solutions to reduce student delays in attending Al-Qur'an and Tafsir Science lectures.